Behavior Changes in Quinpirole Obsessive-Compulsive Disorder Rats Treated with 6-Hydroxydopamine and the Corresponding Dopaminergic Compulsive Loop Mechanism - Haowen Zheng; Rui He; Yang Ming; Haiping He; Wei Wang; Ligang Chen; Feilong Gong (Journal of Integrative Neuroscience)
Background: Recent studies suggest that the anterior limb of the internal capsule may be an area of convergence for multiple compulsion loops. In this study, the role of different dopaminergic compulsion loops in the mechanism of obsessive-compulsive disorder (OCD) was investigated by selectively damaging dopaminergic neurons or fibers in the corresponding targets with 6-hydroxydopamine (6-OHDA) and depicting the anatomical map of various compulsion loops located in the anterior limb of the internal capsule. Methods: A total of 52 male Sprague Dawley (SD) rats were exposed to either saline (1 mL/kg, NS group, n = 6) or quinpirole (QNP, dopamine D2-agonist, 0.5 mg/kg, n = 46) twice weekly for 5 weeks. After each injection, the rats were placed on an open field to analyze aspects of their behaviour, including the number of home base visits (NOH), average time between each home base visit (ATBO), and total distance travelled (TDM). After model setup, 46 QNP rats were divided randomly into five groups: 6-OHDA anterior limb of internal capsule (AC) stereotactic injection group (QNP+AC group, n = 10), 6-OHDA mediodorsal thalamic nucleus (MD) stereotactic injection group (QNP+MD group, n = 10), 6-OHDA nucleus accumbens (NAC) stereotactic injection group (QNP+NAC group, n = 10), saline stereotactic injection group (QNP+NS-S group, n = 10), and non-surgical group (QNP+Non-S group, n = 6). In the NS group, rats simultaneously received a 6-OHDA stereotactic injection (NS+6-OHDA-S group, n = 6: AC2, MD2, NAC2). All QNP-treated rats were then continued to be given QNP twice a week for 4 weeks, and their behaviour was observed after each infusion. After 4 weeks, immunofluorescence staining was used to monitor the distribution of dopamine neurons and nerve fibers in different areas of the intervention nerve loops, and quantitative analysis was performed. Results: Compulsive behaviour declined gradually in the QNP+AC and QNP+NAC groups 3 and 4 weeks after surgery, with the QNP+AC group decreasing more rapidly. The QNP+MD group had decreased by 3 weeks after surgery but increased to almost the same level as pre-surgery at 4 weeks post-surgery. Postoperative fluorescence staining and quantitative analysis suggested the number of dopamine (DA) neurons or nerve fibers in the corresponding target area of the 6-OHDA injection were significantly reduced compared with the QNP+Non-S group. Conclusions: 6-OHDA selectively damages the targets of dopaminergic neurons or nerve fibers within the OCD loop, which somewhat alleviates compulsive behaviours. The results suggest that the AC might be the best target for therapeutic interventions for OCD.